ArcGIS FOR MAPPING VETERAN’S SETTLEMENTS IN THE PROVINCE OF UPPER MOESIA - Ana HONCU; Rada VARGA (Journal of Ancient History and Archaeology, 2023)
This article is about mapping the veterans’ inscriptions from Upper Moesia using ArcGIS software. How can this be done and toward what aims? By applying GIS algorithms to these datasets, we can make various maps and queries that allow us to discuss distribution and spatiality from many different angles. Such an experiment provided us the possibility of a better visualization of data in geographic context and allowed us to identify the specific locations of inscriptions and thus draw conclusions about veteran’s settlement